HUBUNGAN ANTARA PROFESIONALITAS TENAGA PENDIDIK DENGAN MUTU PENDIDIKAN DI MADRASAH ALIYAH NEGERI 1 PEKANBARU - Siti Aisyah; Rini Setyaningsih (stit-islamic-village, 2020)
It was a correlational research studying about educator professionality (X variable) and education quality (Y variable) at State Islamic Senior High School 1 Pekanbaru. This research aimed at knowing educator professionality level, education quality level, and the correlation between educator professionality and education quality at State Islamic Senior High School 1 Pekanbaru. The samples were 46 educators at State Islamic Senior High School 1 Pekanbaru that met the requirements of professional educators—educator competence, qualification of education, and certification. The data were analyzed by using Pearson product moment correlational formula. Based on the analysis, it showed that H0 was rejected and Ha was accepted. It meant that there was a positive and significant correlation between educator professionality and education quality at State Islamic Senior High School 1 Pekanbaru. It could be seen from the comparison between robserved 0.694 and rtable 0.361 at 5% significant level with N that was 46, so robserved was higher than rtable (0.694>0.361). The result of linear regression coefficient showed that the probability score or the significance score 0.000 was lower than 0.05 (0.000<0.05). Based on the determination coefficient, it was obtained the score 0.482 or 48.2% and it was rounded up to 48%. It meant that the contribution of educator professionality variable to education quality variable at State Islamic Senior High School 1 Pekanbaru was 48%, and the rest was influenced by other variables that were not explained in this research. So, the professional educators could increase the quality of education.